2018
DOI: 10.1155/2018/9201539
|View full text |Cite
|
Sign up to set email alerts
|

Gynura procumbens Improved Fertility of Diabetic Rats: Preliminary Study of Sperm Proteomic

Abstract: Gynura procumbens (GP) is a medicinal herb that has long been known as anti-inflammatory and antihyperglycaemic. Recently, this herbal extract has been associated with a profertility effect, suggesting its applicability in treating both diabetes and male infertility. In this study, the effects of GP aqueous extract (GPAE) on diabetic rats were investigated through evaluating testes histology and androgen hormone levels as well as the implantation sites of female rats on copulation with the treated male rats. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Diabetes and hyperglycemia result in the increase of endoplasmic reticulum stress [59], which causes changes in the homeostasis of the endoplasmic reticulum, and subsequently reduces protein synthesis [60]. Previous studies also supported our findings [61,62]. An et al [10] reported that no expression of the spermatogenesis regulator protein was recorded in the sperm of diabetic patients compared to normal.…”
Section: Sperm Protein Concentration Protein Expression Via Sds-pagesupporting
confidence: 87%
“…Diabetes and hyperglycemia result in the increase of endoplasmic reticulum stress [59], which causes changes in the homeostasis of the endoplasmic reticulum, and subsequently reduces protein synthesis [60]. Previous studies also supported our findings [61,62]. An et al [10] reported that no expression of the spermatogenesis regulator protein was recorded in the sperm of diabetic patients compared to normal.…”
Section: Sperm Protein Concentration Protein Expression Via Sds-pagesupporting
confidence: 87%
“…Gerbils received oral administration of distilled water (vehicle-treated ischemic group) or GPE-R (30 mg/kg and 300 mg/kg GPE-R-treated ischemic groups) with a feeding needle once a day for 3 weeks before the surgery. Doses of GPE-R were chosen based on previous findings which showed that administration of 150–450 mg/kg of GP aqueous extract improved fertility [ 36 ] and administration of 25–50 mg/kg of GP stem extract (GPE-S) ameliorated ethanol-induced steatosis [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…A pro-fertility agent, Sanrego, is very common intervention in Asian countries in the search for the eradication of male infertility (Luthfi et al, 2017). The plant, also called Blanco, with wide Lunasia amara diversity has been generally accepted as an alternative medicine (Kamaruzaman et al, 2018). for male who constitute about 50% of all global infertility cases (Agarwal et al, 2015).…”
Section: Phytochemicals and The Integrity Of Reproductionmentioning
confidence: 99%